Sulfisoxazole Elicits Robust Antitumour Immune Response Along with Immune Checkpoint Therapy by Inhibiting Exosomal PD‐L1. Issue 5 (20th December 2021) - Shin, Jung Min; Lee, Chan‐Hyeong; Son, Soyoung; Kim, Chan Ho; Lee, Jae Ah; Ko, Hyewon; Shin, Sol; Song, Seok Ho; Park, Seong‐Sik; Bae, Ju‐Hyun; Park, Ju‐Mi; Choe, Eun‐Ji; et al.
Abstract: Despite their potent antitumor activity, clinical application of immune checkpoint inhibitors has been significantly limited by their poor response rates (<30%) in cancer patients, primarily due to immunosuppressive tumor microenvironments. As a representative immune escape mechanism, cancer‐derived exosomes have recently been demonstrated to exhaust CD8 + cytotoxic T cells. Here, it is reported that sulfisoxazole, a sulfonamide antibacterial, significantly decreases the exosomal PD‐L1 level in blood when orally administered to the tumor‐bearing mice. Consequently, sulfisoxazole effectively reinvigorates exhausted T cells, thereby eliciting robust antitumor effects in combination with anti‐PD‐1 antibody. Overall, sulfisoxazole regulates immunosuppression through the inhibition of exosomal PD‐L1, implying its potential to improve the response rate of anti‐PD‐1 antibodies. Abstract : Biogenesis of cancer‐derived exosomal PD‐L1, responsible for the low response rates of the immune checkpoint inhibitors, is remarkably inhibited by sulfisoxazole as an endothelin receptor A‐selective antagonist. When orally administered to the tumor‐bearing mice, sulfisoxazole reinvigorates exhausted T cells, thereby eliciting potent antitumor effects in combination with an anti‐PD‐1 antibody.